Industrial contracting , collective bargaining and wages in Australia. - Peetz, D.; Preston, Alison (Blackwell Publishing, 2009)
We examine wages in Australia under federally registered individual contracts and collective agreements (CAs) using unpublished data from a national earnings survey. The distribution of earnings under registered individual contracts was more unequal than under CAs. Average and median earnings under registered individual contracts were lower than under CAs. There was little evidence that individual contracting raised wages through raising productivity. The link between contracting and pay appears contingent, varying between occupations, industries, and firm size bands and dependent upon employees' position in the labour market and employers' use of union avoidance strategies. This has implications for the interpretation of studies of union wage effects.